2019
DOI: 10.1177/0271678x19892657
|View full text |Cite
|
Sign up to set email alerts
|

Mild metabolic stress is sufficient to disturb the formation of pyramidal cell ensembles during gamma oscillations

Abstract: Disturbances of cognitive functions occur rapidly during acute metabolic stress. However, the underlying mechanisms are not fully understood. Cortical gamma oscillations (30–100 Hz) emerging from precise synaptic transmission between excitatory principal neurons and inhibitory interneurons, such as fast-spiking GABAergic basket cells, are associated with higher brain functions, like sensory perception, selective attention and memory formation. We investigated the alterations of cholinergic gamma oscillations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 234 publications
(507 reference statements)
3
13
0
Order By: Relevance
“…The vulnerability of PV+ FSI is a particularly important issue, and it is presently unclear to which extent their altered function contributes to impaired post-hypoxic network activity (Johansen et al, 1983;Nitsch et al, 1989;Moga et al, 2002;Wang, 2003;Elzoheiry et al, 2019;Povysheva et al, 2019). Earlier studies found unchanged numbers of PV-IN in contrast to reduced CA1 pyramidal cell numbers several days after HI in vivo (Johansen et al, 1983;Nitsch et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The vulnerability of PV+ FSI is a particularly important issue, and it is presently unclear to which extent their altered function contributes to impaired post-hypoxic network activity (Johansen et al, 1983;Nitsch et al, 1989;Moga et al, 2002;Wang, 2003;Elzoheiry et al, 2019;Povysheva et al, 2019). Earlier studies found unchanged numbers of PV-IN in contrast to reduced CA1 pyramidal cell numbers several days after HI in vivo (Johansen et al, 1983;Nitsch et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Calciumbinding properties of parvalbumin are discussed to reduce neurotoxic effects of calcium overload during HI (Tortosa and Ferrer, 1993). However, more recent studies indicate impaired function of inhibitory neurons compared to excitatory neurons after transient metabolic insults (Moga et al, 2002;Wang, 2003;Elzoheiry et al, 2019;Povysheva et al, 2019). It is important to note the methodical differences in those studies in terms of insult severity and outcome measures (histological cell death versus electrophysiological function).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, [K + ] o rarely exceeds 0.5 mM from a baseline of 3.0 mM during gamma oscillations reflecting the maintenance of K + homeostasis (Kann et al., 2011, 2016; Somjen, 2002), which differs from the larger [K + ] o transients induced by artificial repetitive electrical stimulation in situ and in vivo (Heinemann & Lux, 1977; Kann et al., 2003; Liotta et al., 2012). Conversely, gamma oscillations are exquisitely sensitive to metabolic and oxidative stress (Elzoheiry et al., 2019; Huchzermeyer et al., 2008; Papageorgiou et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the effects of GM-CSF on microglianeuron interactions in organotypic hippocampal slice cultures of the rat, which feature well-preserved cytoarchitecture and functional neuronal networks (Figs. 2 and 3) [30,32,37,44]. Slice cultures inherently lack leukocyte infiltration during experimental exposures and thus permit to explore the reactivity of microglia in the absence of invading granulocytes, monocytes, and lymphocytes [22][23][24].…”
Section: Exploring Microglia-neuron Interactions In Situmentioning
confidence: 99%